If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(h + 3) = (h + -3) Reorder the terms: 7(3 + h) = (h + -3) (3 * 7 + h * 7) = (h + -3) (21 + 7h) = (h + -3) Reorder the terms: 21 + 7h = (-3 + h) Remove parenthesis around (-3 + h) 21 + 7h = -3 + h Solving 21 + 7h = -3 + h Solving for variable 'h'. Move all terms containing h to the left, all other terms to the right. Add '-1h' to each side of the equation. 21 + 7h + -1h = -3 + h + -1h Combine like terms: 7h + -1h = 6h 21 + 6h = -3 + h + -1h Combine like terms: h + -1h = 0 21 + 6h = -3 + 0 21 + 6h = -3 Add '-21' to each side of the equation. 21 + -21 + 6h = -3 + -21 Combine like terms: 21 + -21 = 0 0 + 6h = -3 + -21 6h = -3 + -21 Combine like terms: -3 + -21 = -24 6h = -24 Divide each side by '6'. h = -4 Simplifying h = -4
| 29=19+a | | 4y-12=60 | | 3x^2+2x+3y^2-7y-10=0 | | -22=a+29 | | 26-8t=-30 | | -10.1f-19.29=14.28-8.3f-13.05 | | -132=11n | | 4p-6=3+4p | | 8xz=15 | | 4t=12.16+5.6t | | 28-6(2x-9)=60 | | 7x+x-6=2(x+9) | | 6x^2=-14x+40 | | -22+m=26 | | 9x-13=95 | | 11(x-2)-410=2(2x-4)+49 | | -23+n=-15 | | 11(x-2)-410=2(2x-4) | | 3x^2=33 | | 9.96=6.8g | | 1.76-4.3r=-18r-6.46 | | 4w^2+3=9 | | 5x+10-2x-3x+2+4x=0 | | 6(12)-3y=12 | | 4x^2=8x-1 | | 6(0)-3y=12 | | 6x-3(0)=12 | | -7.1d+11.96=-7.54-8.6d | | -8(t+4)=0 | | e=mc^2 | | 10b-35= | | 18+p=3 |